Perancangan Aplikasi Sistem Informasi Wisata Alam di Kota Pandeglang, Provinsi Banten, Berbasis Web dengan Metode Waterfall Menggunakan PHP dan MySQL - Supriadi, Edi; Nurcahyo, Widyat; Faizah, Novianti Madhona (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
A web-based information system plays a crucial role in providing access to information without requiring visitors to physically visit a location. Pandeglang City, located in Banten Province, is home to various natural tourist attractions that remain largely unknown to travelers. Therefore, there is a need for an application that allows both local and international visitors to obtain information about the natural tourist spots in the area. This study aims to design a web-based information system to provide data about the locations and facilities of tourist attractions in Pandeglang City. The Waterfall method is applied in the development process, starting with needs analysis, system design, code writing, testing, and system implementation. The application will assist visitors in learning about tourist spots and supporting facilities around these locations. With the availability of this application, it is expected that tourists can more easily plan their visits. The results of this system's development will simplify access to information about natural tourist attractions in Pandeglang City, potentially increasing tourist visits. This information system is anticipated to positively contribute to the growth of the tourism sector in the region.